Developing Educational App to Boost Students’ Basic English Skills: A Research & Development - Rayyan, Ahmat Ramadana (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
The aim of this research was to identify what media students needed and how to develop it, as well as to determine whether the media was effective in overcoming student problems. This research utilized a research and development design. The population of the research comprised all first-grade students of SMAN 4 Lhokseumawe, which included two classes. In this research, two classes were chosen as samples using simple random sampling. The sample was divided into two groups. The experimental group X.1 consisted of 30 students who were taught using the direct instruction method, while the control group X.2 consisted of 30 students who were taught normally. The data collection techniques used were questionnaires and tests, which included pre-tests and post-tests. The researcher administered questionnaires before conducting the pre-test. Then, the researcher gave the pre-test before providing treatment and the post-test after the treatment. The data were analyzed using the t-test formula. The researcher found that the scores of the t-test were 1.77, 2.21, 1.69, and 2.1, while the score of the t-table at the significance level of 0.05 and df = 58 was 1.67. This indicated that the t-test was higher than the t-table. Thus, based on the criteria, the alternative hypothesis (Ha) of this research was accepted, and the null hypothesis (Ho) was rejected. This indicated that using the educational application was effective in enhancing the basic English skills of first-grade students at SMAN 4 Lhokseumawe.